Affective geopolitics: Anxiety, pain, and ethics in the encounter with Syrian refugees in Turkey. (November 2020) - Gökarıksel, Banu; Secor, Anna J
This paper explores the affective making of geopolitics through an analysis of how long-term residents of Turkey narrate their encounters with displaced people from Syria. Situating these narratives in relation to Turkey's policies and practices concerning the Syrian war and Syrian refugees, our project asks: What are the affective dimensions of encountering Syrians in Turkey and how do these encounters unfold an embodied geopolitics on the street and in neighborhoods? Our analysis of focus group conversations (conducted between 2014 and 2016 in Istanbul, Konya, and Malatya) centers on three dimensions of the affective geopolitics of the Syrian refugee crisis in Turkey. First, we draw out feelings of threatening proximity, in which the denigration of Syrian bodies and lives converges with the desire for a spatial organization of bodies that would put literal boundaries between "us" and "them." Second, we present how the Adalet and Kalkınma Partisi's geopolitical orientation towards leadership in the Muslim Middle East and official rhetoric regarding Turkey's obligation to the Syrians as part of Muslim unity do not preclude the anxiety citizens express about the embodied presence of displaced Syrians in their daily lives. And finally, we address the politics of pain and the problems of translation in the encounter with the other. Here, we argue that the imminent, embodied, and affective challenge posed by the arrival of more than three million Syrians in Turkey concerns the ethics of how to hear, understand, and respond to the pain of others.